Hubungan Ukuran Tubuh dengan Bobot Badan dan Bobot Karkas pada Kambing Jawarandu Jantan - Munawarah, Ratu Aisyah; Muthalib, R.A; Farizal, Farizal; Afzalani, Afzalani; Sulaksana, Indra; Hoesni, Fachroerrozi; Pradana, Erbid Dwi (Universitas Batanghari Jambi, 2025)
This study was to determine how long, chest circumference, shoulder height, and hip height, as well as other body measurements, fall with body weight and carcass weight. Regression and correlation analysis were used after data were collected directly through observation. Mat Beken Farm in Jambi was the source of this data. Male Jawarandu goats were selected as samples for this study. Goats at the ages of (2-2.5) years and (3-3.5) years were known to have permanent incisor teeth, weighing, and body measurements such as length, chest circumference, shoulder height, and hip height. This study found that in the 12 and I3 age groups, chest circumference was the most significant measurement in ranking with body weight and carcass weight, with a very significant correlation value (P